Effect of Age on Selected Plasma Indices of Biochemical and Mineral Metabolism in Two Strains of Broiler Chickens - Arzour-Lakehal , Nedjoua; Benlatreche, Cherifa; Boukerrou, Abderrahmane; Siliart, Brigitte (International Journal of Poultry Science, 2015)
The aim of the study was to determine changes in plasma concentrations of 12 biochemical parameters of lipid, protein, carbohydrate and mineral metabolism in two strains of broiler chickens and to compare blood profile of the two groups. The investigation was conducted on 160 broiler chickens: 80 broilers Isa 15 strain and 80 broilers Arbor Acres strain. For the two strains, samples were held at 7, 14, 35 (59 days for Isa 15 strain, 57 days for Arbor Acres strain) and then analyzed. Most of the estimated parameters were age-dependent. Concentrations of plasma cholesterol and triglycerides showed a significant decrease along the experimental period (p<0.05). Concentrations of plasma glucose decreased significantly (p<0.05) until the 35th day of age in the two groups and then augment statistically. A significant increase (p<0.05) in plasma concentrations of total protein, creatinine and calcium was observed in the two strains during the experimental period. A significant decrease (p<0.05) in plasma uric acid and plasma phosphorus was found in the two strains between the 7th day and the end of the fattening period. Plasma magnesium showed a constant significant decrease (p<0.05) during all the experimental period in the two groups. Plasma urea and plasma albumin remained low in the two strains. Plasma concentrations of iron decreased (p<0.05) until the 35th day of age in the two groups. A significant difference (p<0.05) in plasma glucose, plasma uric acid, plasma creatinine, plasma calcium, plasma magnesium and plasma phosphorus was found between Isa 15 strain and Arbor Acres strain. The given results may be helpful for evaluating the health status, so that the genetic potential for growth and production of the bird is fully expressed. They will expand the current knowledge on the changes in the biochemical profile of broiler chickens.